Contributions to Islamic economic theory : a study in social economics - Choudhury, Masudul Alam. (London : Palmgrave Macmillan, 1986)
This paper aims to provide an economic rationale for Islamic finance.Its methodology is simple. It starts with listing the contributions to economic analysis relevant to the required rationale in the theories of banking, finance, price, money and macroeconomics, to identify the main rationale for Islamic finance. A concise description of the author$1 (Bs model for an Islamic economic system, within which Islamic finance can be operational, is provided.s
Includes bibliographical references and index.
aia 09/04/2018
Loans
Keywords: Economics $1 (BReligious aspects $1 (BIslam.s; Economics; Islam; Islamic Countries